The European encounter with Hinduism in India - Schouten, Jan Peter, 1949- (Currents of Encounter, 2020)
"In The European Encounter with Hinduism Jan Peter Schouten offers an account of European travellers coming into contact with the Hindu religion in India. From the thirteenth century on, both traders and missionaries visited India and encountered the exotic world of Hindus and Hinduism. Their travel reports reveal how Europeans gradually increased their knowledge of Hinduism and how they evaluated this foreign religion. Later on, although officials of the colonial administration also studied the languages and culture of India, it was - contrary to what is usually assumed - particularly the many missionaries who made the greatest contribution to the mapping of Hinduism".